Profitability Analysis of Conventional and Islamic Banks in Bangladesh: A Comparative Study - Alam, Md. Shahbub; Hossain, G. M. Anwar; Amin, Dr. Md. Ruhul (International Journal of Business, Management and Economics, 2025)
This comparative study on profitability analysis of conventional and Islamic banks in Bangladesh from 2018 to 2022 gives an insightful financial performance of the two modes of banking stream. For the analysis, five conventional banks and five Islamic banks were chosen randomly. Financial ratios are calculated from the respective bank’s annual financial reports and the Central bank’s data to measure profitability. Ten profitability indicators are used to analyze data, comparing the results of two types of banks, and finally, the ANOVA test shows the differences in profitability measures at a 5% level of significance. Conventional banks are performing better in terms of NNII, Spread, Burden, OP, NP, ROA & ROE, but Islamic banks are performing better regarding profit earned, profit paid, and OOE. The differences in profit earned ratio, profit paid ratio, and Spread ratio are significant, which indicate that trends are not identical in conventional and Islamic banks, but the differences in NNII ratio, OOE ratio, Burden ratio, OP ratio, NP ratio, ROA, ROE are not significant which indicate that trends are identical. Deposit and investment trends of Islamic banks are better than conventional banks, and it shows Islamic banks have good prospects in the near future. Overall findings show that conventional banks are doing comparatively better than Islamic banks in terms of profitability measures